Computerized Training of Working Memory in Children with ADHD-A Randomized, Controlled Trial - Klingberg, Torkel; Fernell, Elisabeth; Olesen, Pernille J; Johnson, Mats; Gustafsson, Per; Dahlstrom, Kerstin; Gillberg, Christopher G; Forssberg, Hans; Westerberg, Helena (Journal of the American Academy of Child and Adolescent Psychiatry, 2005)
Objective: Deficits in executive functioning, including working memory (WM) deficits, have been suggested to be important in attention-deficit/hyperactivity disorder (ADHD). During 2002 to 2003, the authors conducted a multicenter, randomized, controlled, double-blind trial to investigate the effect of improving WM by computerized, systematic practice of WM tasks. Method: Included in the trial were 53 children with ADHD (9 girls; 15 of 53 inattentive subtype), aged 7 to 12 years, without stimulant medication. The compliance criterion (>20 days of training) was met by 44 subjects, 42 of whom were also evaluated at follow-up 3 months later. Participants were randomly assigned to use either the treatment computer program for training WM or a comparison program. The main outcome measure was the span-board task, a visuospatial WM task that was not part of the training program. Results: For the span-board task, there was a significant treatment effect both post-intervention and at follow-up. In addition, there were significant effects for secondary outcome tasks measuring verbal WM, response inhibition, and complex reasoning. Parent ratings showed significant reduction in symptoms of inattention and hyperactivity/impulsivity, both post-intervention and at follow-up. Conclusions: This study shows that WM can be improved by training in children with ADHD. This training also improved response inhibition and reasoning and resulted in a reduction of the parent-rated inattentive symptoms of ADHD.